ETHNOSCIENCE-BASED COMIC STRIPS AS LEARNING MEDIA TO IMPROVE SOCIAL SKILLS OF ELEMENTARY SCHOOL STUDENTS: INTEGRATED SCIENCE AND SOCIAL STUDIES - Yuliana Yuliana; Rambang Muharramsyah; Nadia Aldyza (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
The rapid development of digital media and the decline of students’ social interaction skills highlighted the need for innovative learning media, such as ethnoscience-based comic strips as learning media, to effectively enhance elementary school students’ social skills. This study was conducted to investigate the effectiveness of ethnoscience-based comic strips as instructional media in enhancing the social skills of elementary school students. A quasi-experimental method with a non-equivalent control group design was applied. The experimental group was taught using ethnoscience-based comic strips, while the control group received instruction through conventional teaching methods. The participants consisted of 60 students selected through cluster sampling techniques. Data were gathered using a questionnaire, with validity tested using Aiken’s V index and reliability measured through Cronbach’s alpha coefficient. The data analysis employed a descriptive quantitative approach. The findings revealed a significant difference in students’ social skills between the experimental and control groups (Sig = 0.00 < α). There was a notable improvement in social skills, as indicated by an increase in the average percentage from 75% (good category) to 81% (very good category) based on teachers’ questionnaire assessments. Furthermore, the effectiveness test using the Gain Score indicated an improvement of 0.61, categorized as good, based on pretest and posttest results. Observations of student activities also showed a positive outcome, with a percentage of 80%, meeting the criteria for good performance. Theoretically, this study suggests that ethnoscience-based comic strips, designed with engaging visuals and integrated social skill components, serve as an effective learning medium.